War against plastic, a genuine commitment of Denpasar City in prevailing Tri Hita Karana concept - Ida Bagus Komang Surya Werdiyasa (Bali Tourism Board, 2019)
On the first day of 2019, Government of Denpasar City, Bali, published a new regulation, namely Mayor Regulation No. 36/2018 (Perwali No. 36 Tahun 2018) to minimize the usage of plastic, as single used shopping Bags in Denpasar City. The regulation has been active since January 1, 2019. Plastic has become part of modern days civilization. Various industries apply the usage of plastic, due to its durability, lightweight and easy to afford. However, beyond all the convenience it offers, turns out a terrible fact awaits; a hazardous plastic waste that impossible to decompose naturally. Plastic is classified into seven types according to its composition, they are Polyethylene Terephthalate (PET), High-Density Polyethylene (HDPE), Polyvinyl Chloride (PVC), Low-Density Polyethylene (LDPE), Polypropylene (PP), Polystyrene (PS) and the ‘O.’ Plastic is recyclable, nevertheless, it mostly ended in the ocean, due to the finite availability of plastic recycler in Indonesia, as well as low social awareness in keeping the environment clean. Mayor Regulation No.36/2018 is an effort of Denpasar city to minimize single-use plastic bag. The Government through the local regulation suggests shopping centers and modern stores provide environmental-friendly alternative bags with biodegradable standard or permanent bags that can be used repeatedly, to reduce society’s dependence on using single-use plastic bags when shopping. The regulation is a clear example of Denpasar City in preserving the environment based on the philosophical foundation of the concept of Tri Hita Karana. It is a Balinese concept to maintain harmonious relationships between humans to God, among humankind, as well as human and their environment.